On the relationship between consumer-brand identification, brand community, and brand loyalty - Coelho, P. S.; Rita, P.; Santos, Z. R. (Journal of Retailing and Consumer Services, 2018)
Recent studies have highlighted the importance of social media brand communities to brand loyalty. This paper aims to stress the role of the brand in that relationship, suggesting a conceptual model in mass-market products in which consumers’ engagement in social media brand communities, brand identity, and consumer-brand identification are related to brand outcomes, such as trust and loyalty. A qualitative analysis was conducted, through in-depth interviews with experts and focus group discussions with consumers, so as to evaluate their experience with brands on social media. The findings indicated that in mass-markets, consumers engaged in social media brand communities may develop positive attitudes towards the brand, such as trust and loyalty, and that consumer-brand identification may have a fundamental role in transforming consumer-brand community interactions into consumer-brand relationships.